My quarantine landscapes: A personal inquiry into the COVID-19 lockdown experience through drawings. (1st July 2022) - Demirtoka, Sezin
This article presents an art-based personal inquiry into the author's experience of the COVID-19 lockdown in 2020. Drawing was used as a way to document, process and regulate feelings during the lockdown. The author revisited these drawings over the course of the following year, engaging with them through imaginative dialogues and creative writing, and looking for patterns to make meaning of them. This inquiry highlighted themes of existential issues around death and life, longing for connectedness to nature and other humans, and the toll of home confinement on the lived body. The author reflects on how artistic inquiry helped her approach an anxiety-provoking situation with curiosity, become aware of existential issues that the pandemic had brought up and treat them with intentionality and authenticity.